Effect of aglepristone (RU534) administration during follicular phase on progesterone, estradiol‐17β and LH serum concentrations in bitches. Issue 12 (10th November 2020) - Troisi, Alessandro; Polisca, Angela; Cardinali, Lucia; Orlandi, Riccardo; Brecchia, Gabriele; Menchetti, Laura; Zerani, Massimo; Maranesi, Margherita; Di Mari, Walter; Verstegen, John Paul
Abstract: Aglepristone was administered in bitches during the follicular phase to evaluate its effects on progesterone, estradiol‐17β and LH serum concentrations. Ten German Shepherds were divided into two groups (treated n = 5; control n = 5). Treated bitches received 10 mg/kg BW of aglepristone subcutaneously during the early follicular phase, 24 hr after and then 7 days later. The control group was injected, at the same time periods, with saline solution (0.3 ml/kg BW). For the steroid evaluations, blood was collected daily from the onset of proestrus until the first day of cytological dioestrus. For LH base‐line serum determination, blood was also collected every 20 min for 2 hr at the onset of proestrus. For LH surge identification, blood was collected daily (every 6 hr) starting from the day of the first administration of aglepristone or saline solution until the first day of dioestrus. All animals ovulated but the treated group presented longer ovulation‐dioestrus intervals than the control group (5.2 ± 2.2 days p < .05). Serum concentrations of the evaluated hormones were similar between experimental animals except for serum LH. Indeed, no LH peaks were detected in the treated group while LH surges were clearly observed in the control group (9 ± 1 days after the beginning of proestrus. In particular, the area under the curve for LH was significantly lower in treated than control animals (12 ± 4 ng/ml x Day; p = .01). In conclusion, administrations of aglepristone during the follicular phase of the bitch does not affect the steroid hormone patterns but does prevent the occurrence of a LH surge. This work raises significant questions and opens perspectives concerning the mechanisms of ovulation in bitches.